The genesis of restrictions and special requirements established during public service (Law and Safety, 2023)
The article proposes to single out the four periods of development of the administrative and legal foundations of the public service and special requirements for the activities of public servants.The legal support of public service during the entry of Ukrainian lands into the Lithuanian-Polish state was associated with the emergence and approval of two main restrictions applied to public servants, which consisted in property and educational qualifications.The legal provision of public service during the Cossack era is characterized by the formation of public service as a separate independent institution, especially since 1918, when a number of requirements and restrictions were formulated for public servants, namely: age, residence, citizenship, competence, qualifications.The legal support of the public service of the Soviet model provided for the application of template requirements for public servants (age, higher education in the specialty, work experience, business and moral qualities), as well as restrictions on part-time jobs that were applied to individual public servants (for example, prosecutors and judges).The legal support of the public service of independent Ukraine is divided into the following stages:1) 1991–1992 – a transitional stage to the adoption of the Law of Ukraine “On Public Service”, during which Soviet legal acts continued to operate and, in parallel, laws of Ukraine were adopted that regulated the activities of certain categories of public servants;2) 1993–1995 – the stage of formation of the institution of public service of the Ukrainian state and the registration of certain general anti-corruption restrictions on public servants without their clear systematization;3) 1995–2011 – the stage of stagnation, which begins with episodic expansion and specification of restrictions during public service, as a result of the adoption of the Law of Ukraine “On Combating Corruption”;4) 2011–2014 – the stage of development is determined by the course of European integration and the public's request for the fight against corruption as the main determinant of the destruction of the institution of public service;5) 2015 to the present is the latest stage, which began with the transformation of state and public institutions, as well as the adoption of a number of European integration legal acts.
Keywords: public service; restrictions; requirements; anti-corruption legislation; part-time employment; conflict of interest.